Bridging housing & health: a toolkit for local public health action - Van Brunt, Anna (My University, 2025)
Health and housing are inextricably linked. An individual or family can't be their healthiest and contribute to their community in the highest capacity if the space they are living in is hazardous to their health. Alternatively, it is difficult to invest in one’s health if they are spending most of their income on housing costs, creating an inability to save for the future or breaking cycles of poverty that dramatically influence health. These systems are marked by inequalities that are not the fault of individuals or communities, but inequities brought about by systems that were set up to harm communities of color and those with other historically marginalized backgrounds from our country’s founding. At the local level, many public health interventions stem from Community Health Assessment (CHA) or Community Health Needs Assessment (CHNA) data that demonstrates residents' health is being impacted by their housing quality and costs. In the Kansas City area, these results have led public health departments and health systems to prioritize housing in their Community Health Improvement Plans (CHIPs). Most public health practitioners, however, are not trained in the housing system and lack the knowledge on successful interventions that address housing costs. This Applied Practice Experience included three one-on-one interviews with these public health practitioners whose experience doing this work and six relevant meetings which ultimately informed the creation of a guide for public health action in housing solutions. This Applied Practice Experience was completed in early 2025 at the Mid-America Regional Council (MARC) in Kansas City, Missouri. MARC is the metropolitan Planning Organization and Council of Governments for the Kansas City region and provides a variety of services and programs to residents and communities. Counties include Leavenworth, Wyandotte, Johnson, and Miami in Kansas and Ray, Clay, Jackson, Cass, and Platte counties in Missouri.
Keywords: Social determinanats of health; Health equity; Community health; Improvement plan